2020
DOI: 10.1007/s10551-019-04422-2
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Everyday Consumption Ethics: A Moral Economy Approach

Abstract: As research on ethical consumers and consumption practices has continued to grow, a complimentary body of work concerned less with ethical consumption but more with ethics in consumption has emerged. Problematizing the divide between ethical and non-ethical consumption, this stream of research focuses on the domain of everyday and explores the moral struggles individuals face while engaging in ordinary consumption practices. However, the attention on the ordinary runs the risk of obscuring the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…Many studies have already shown such potential by investigating the intersections of politics, religion and the market (e.g. Husain et al, 2019; Jafari and Süerdem, 2012; Karababa and Ger, 2011; Sandikci, 2021; Sandikci and Ger, 2010; Süerdem, 2013), poverty and displacement (e.g. Saatcioglu et al, 2016; Üstüner and Holt, 2010; Yurdakul et al, 2017), politics and institutional corruption (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have already shown such potential by investigating the intersections of politics, religion and the market (e.g. Husain et al, 2019; Jafari and Süerdem, 2012; Karababa and Ger, 2011; Sandikci, 2021; Sandikci and Ger, 2010; Süerdem, 2013), poverty and displacement (e.g. Saatcioglu et al, 2016; Üstüner and Holt, 2010; Yurdakul et al, 2017), politics and institutional corruption (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among the key topics studied by prior research are price consciousness (Sood and Nasu, 1995), grocery spending (Kurt et al ., 2018), and food consumption (Minton et al ., 2020). There has also been a significant interest in understanding how religious beliefs (e.g., “All wealth belongs to God”) influence outcomes in the domains of consumer materialism (e.g., Belk, 1983; Pace, 2013; Leary et al ., 2016), consumer ethics (e.g., Vitell et al ., 2005; Sandikci, 2021), and luxury consumption (e.g., Geiger‐Oneto and Minton, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The role religion plays in crafting the social and cultural environments of customers (Assadi, 2003) means that companies need to accommodate for these in marketing communications and product development in order to be more positively evaluated by potential customers. Regulations support everyday buying behaviour (Assadi, 2003;Floren, Rasul and Gani, 2019), hence, it integrating religion into everyday consumption ethics (Sandikci, 2020). For example, Islamic rules speak to the approach to spending and managing money (Assadi, 2003;Alam, Mohd and Hisham, 2011).…”
Section: Regulation Adherencementioning
confidence: 99%